The role of TQM tools in prioritizing the process of improvement: Application Research in the Baghdad Company for soft drinks – private corporation (Journal of Accounting and Financial Studies ( JAFS ), 2019)
TQM plays a major role in restructuring businesses in line with their potentials and their constantly changing technological environment. Business organizations need to improve their system and achieve an advantage that makes them able to enter the competitive arena.. However, the process of improvement is expensive in all aspects and can not be applied in a comprehensive manner. Therefore the problem research could be defined as How to determine the priority of the improvement process and where to start. The research aims to clarify the role of TQM tools in the process of improvement and to show that role through application in a case study. The study deducted a set of conclusions, the most important of which is the possibility of using the analytical tools, within the framework of TQM, to diagnose the relative importance of the constraints or sources of disruption according to the amount of production loss as a result of that disruption, and accordingly determine where to start theprocess of improvement. The researchers recommends the need to early diagnosis of possible limitations or weaknesses and adoption of preventive measures through appropriate changes in the production system and devices or improve the management of operations and development of means of monitoring the process of production in all stages and cost-benefit analysis and the use of TQM tools in determining any constraints that must be addressed.